Human rights in Soviet society - Konstantin U. Chernenko. (International Publishers, 1981)
Translation of: SSSR-KPSS, sotsialisticheskoe obshchestvo, prava cheloveka. English title of Russian ed.; USSR--The Communist party, socialist society, human rights. Moscow, 1981.